Preparation of chitosan scaffolds for tissue engineering using supercritical fluid technology - Duarte, Ana Rita C. (2010)
The aim of this study was to evaluate the possibility of preparing chitosan porous matrixes using supercritical fluid technology. Supercritical immersion precipitation technique was used to prepare scaffolds of a natural biocompatible polymer, chitosan, for tissue engineering purposes. The physicochemical and biological properties of chitosan make it an excellent material for the preparation of drug delivery systems and for the development of new biomedical applications in many fields from skin to bone or cartilage. Immersion precipitation experiments were carried out at different operational conditions in order to optimize the processing method. The effect of different organic solvents on the morphology of the scaffolds was assessed. Additionally, different parameters that influence the process were tested and the effect of the processing variables such as polymer concentration, temperature and pressure in the chitosan scaffold morphology, porosity and interconnectivity was evaluated by micro computed tomography. The preparation of a highly porous and interconnected structure of a natural material, chitosan, using a clean and environmentally friendly technology constitutes a new processing technology for the preparation of scaffolds for tissue engineering using these materials.